2020
DOI: 10.15766/mep_2374-8265.10924
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a Low-Resource Simulation Emergency Medicine Curriculum in Nepal

Abstract: Introduction: High-fidelity medical simulation is widely used in emergency medicine training because it mirrors the fast-paced environment of the emergency department (ED). However, simulation is not common in emergency medicine training programs in lower-resourced countries as cost, availability of resources, and faculty experience are potential limitations. We initiated a simulation curriculum in a low-resource environment. Methods: We created a simulation lab for medical officers and students on their emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…In 2015, only four individuals had completed their postgraduate training in emergency medicine in Nepal [7]. However, new programs and initiatives have been implemented in Kathmandu, where collaborative international emergency medicine training has been established [32], and new research studies have emerged describing possible points of improvement in the emergency medicine curriculum [33]. Even though research on Nepalese emergency medicine and treatment has emerged, most studies are conducted in Kathmandu with only a few studies coming from the remaining part of Nepal.…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, only four individuals had completed their postgraduate training in emergency medicine in Nepal [7]. However, new programs and initiatives have been implemented in Kathmandu, where collaborative international emergency medicine training has been established [32], and new research studies have emerged describing possible points of improvement in the emergency medicine curriculum [33]. Even though research on Nepalese emergency medicine and treatment has emerged, most studies are conducted in Kathmandu with only a few studies coming from the remaining part of Nepal.…”
Section: Discussionmentioning
confidence: 99%
“…Skill labs or simulation centers are not essential for a high-quality simulation session, in fact Wang et al (24) demonstrated that a sustainable simulation lab can be constructed and potentially play a supportive role in developing an emergency medicine curriculum even in countries with limited resources. Further, team-based sessions with experienced facilitators can add to the realism of simulation scenarios and deepen the degree of participant immersion.…”
Section: Crisis Resource Managementmentioning
confidence: 99%